Redução de desoxinivalenol em grãos de trigo contaminados naturalmente, utilizando gás amônia em diferentes tempos e concentrações - De Bastiani, Carlos Miguel (2024)
The presence of mycotoxins, such as deoxynivalenol (DON) in wheat, has been a major obstacle to the growth of wheat farming in Brazil. This problem generates low product liquidity and reduces its quality, discouraging producers from investing in cultivation. The deactivation of DON in wheat, through the use of ammonia, has been presented as a viable alternative, contributing to the use of grains that are currently rejected for food production, as they present concentrations of DON above those permitted by legislation. The objective of this study was to verify the effect of ammonia gas at different times and concentrations on the deactivation of deoxynivalenol (DON) in wheat grains. To carry out the evaluation, a wheat sample naturally contaminated with 1,725 μg/kg (ppb) of DON was used. This sample was treated with ammonia gas at concentrations of 0%, 1%; 1.5% and 2%, for contact times of 2 hours, 12 hours, 1 day, 5 days and 10 days, with 6 repetitions per treatment. For each sample, DON quantification analyzes were carried out before and after treatment with ammonia gas by high-performance liquid chromatography coupled to mass spectrometry (LC-MS/MS). It was observed that, as the concentration and exposure time of ammonia gas in wheat grains increased, the greater the deactivation of DON, obtaining a reduction of up to 86.5%. In the bromatological analysis, an increase in protein and ether extract of 12.5% and 34.6%, respectively, was observed, and a reduction of 8.36% in starch. In ash and crude fiber, no significant changes were observed. The results obtained are promising in the control of DON in wheat grains. New research needs to be carried out to understand the changes that occurred in its bromatological composition after treatment with ammonia gas.